Analysis of Medical Service Performances For BPJS's Patients And Non-BPJS's Patients At Surgery Room In District General Hospital : Analisis Kinerja Pelayanan Medis Pada Pasien BPJS Dan Non BPJS Di Ruang Operasi RSUD X - N. Imas Susanti; Budi Hartono (STIKes Hang Tuah Pekanbaru, 2019)
Background: According to Law No. 36 of 2009 on Health, that the government is responsible for the implementation of public health services through Badan Penyelenggara Jaminan Sosial (BPJS). The implementation of these policy lead highly medics’ turn over and declining medics’ performance at the surgery room, such as: postponed the surgery, reschedule the surgery, low patient’s informed concern, and medics’ disappointed for the amount of incentive. Methods: This researches use cross sectional design, conduct a preliminary research study to the 10 respondents, distributed the draft questionnaire to the 15 respondents for the first test of validity and reliability the questionnaire’s questions, distribute final questionnaire to respondents in the surgery room totaling 25 medics’ respondents, and then processing & analyzing data using multiple linear regression model. To strengthen that quantitative research method, this research also does qualitative method analyzing by interviewing 5 expertises as informant Results: The results of research, shows that there are six factors that should affect to the services performance for BPJS and Non BPJS patients, that are: age of medics, length of employment, motivation, competence, incentives, and time of incentive payments. Based on modeling factors (based on classic model) describes that all of those factors are simultaneously affecting to the service performance for both of BPJS and Non BPJS patients in significantly. Conclusion: The difference in the performance of doctors between BPJS and Non BPJS patients that occur is certainly not in accordance with the mandate of the Act No. 36 of 2009 concerning Health, where the principle of patient care must be based on equality and justice. In this context, hospital management needs to manage wiser and wiser regarding the services of medical personnel in this hospital